Component Discrimination and Anti-skin-aging Potency of Emprit and Red Ginger Essential Oil: Chemometric, Molecular Docking and Molecular Dynamics Study - Badrunanto, Badrunanto; Asoka, Shadila Fira; Wahyuni, Wulan Tri; Farid, Muhammad; Wahyudi, Setyanto Tri; Batubara, Irmanida (Syarif Hidayatullah State Islamic University, 2023)
Emprit and red ginger essential oils (EOs) are natural sources of antioxidants that have the potential to be used in cosmetics, one of which is as an anti-skin-aging. The aim of this study was to determine the component differences and anti-skin-aging potential of the two EOs. The components were determined by GC-MS, while discrimination was done by chemometric. The potential of the components as the anti-skin-aging were evaluated by molecular docking and molecular dynamics (MD) simulations. A total 66 components were identified in both EOs, where eucalyptol (17.92%) and camphene (15.12%) were the main component in emprit and red ginger, respectively. Chemometric analysis revealed two discriminant clusters highlighting their dissimilarity with germacrene D and α-zingiberene are the key markers for differentiation. The docking and MD simulations were demonstrated the four main components of emprit EO, namely α-curcumene, α-zingiberene, β-bisabolene and β-sesquiphellandrene, have the best docking scores and interact with the enzymes with a relatively stable interaction. AdmetSAR evaluation of the four components has shown good bioavailability and declared safe. This study succeeded in revealing two ginger EOs differences based on their components and demonstrated the emprit ginger EO was more promising as a natural anti-skin-aging agent for further research.